Comparison Of Efficacy Of Meloxicam, Ketoprofen And Carprofen As Postoperative Pain Management Agents In Clinical Canine Orthopaedic Surgery - Ranpariya, J.J.; Barvalia, D.R.; Padaliya, N.R.; Javia, C.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present clinical study was carried out on 18 dogs presented to Veterinary College Hospital with various orthopaedic conditions. They were randomly divided into three groups each of 6 animals to compare analgesic efficacy of meloxicam, ketoprofen and carprofen in post-operative orthopaedic pain management. Dogs of group I, received meloxicam @ 0.2 mg/kg b.wt. i/m once followed by oral dose 24 hourly, group II ketoprofen @ 1.5 mg/kg b.wt. i/m once daily and group III carprofen @ 4 mg/kg b.wt. orally 12 hourly, as analgesics for 5 days. Result revealed that in canine orthopaedic cases meloxicam was the best followed by ketoprofen and carprofen.